2020
DOI: 10.3390/nu12071938
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-Hydroxyvitamin D Concentrations Are Associated with Mental Health and Psychosocial Stress in Young Adults

Abstract: We aimed to test the hypothesis that serum 25-hydroxyvitamin D3 (25(OH)D) concentration is associated with mental health and life stress measures in young adults and investigate gender and racial disparities in these associations. This study comprised 327 black and white participants. Depression, trait anxiety, perceived stress, and hostility were measured by the following validated instruments: Beck Depression Inventory (BDI), State-Trait Anxiety Inventory (STAI), Perceived Stress Scale (PSS), and Coo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…A study by Di Nicola et al, 2020, showed that low 25-hydroxyvitamin D serum levels were significantly correlated with greater mental disturbance in patients with mood illnesses during the COVID-19 pandemic ( 65 ). Similar results were reported by Chen et al demonstrated a significant association between low serum 25 (OH) D levels and poor mental health in a large sample of young adults ( 66 ). Moreover, many studies have found some positive impacts of vitamin D supplementation in individuals with clinical depression and vitamin D deficiency ( 60 , 61 , 67 ).…”
Section: Discussionsupporting
confidence: 89%
“…A study by Di Nicola et al, 2020, showed that low 25-hydroxyvitamin D serum levels were significantly correlated with greater mental disturbance in patients with mood illnesses during the COVID-19 pandemic ( 65 ). Similar results were reported by Chen et al demonstrated a significant association between low serum 25 (OH) D levels and poor mental health in a large sample of young adults ( 66 ). Moreover, many studies have found some positive impacts of vitamin D supplementation in individuals with clinical depression and vitamin D deficiency ( 60 , 61 , 67 ).…”
Section: Discussionsupporting
confidence: 89%
“…Studies have shown that Vitamin D-deficient people have increased odds of having clinically significant depression. Various studies conducted in different parts of the world suggest that irrespective of nutrition intake, longitudinal and latitudinal variation for sun exposure, skin pigmentation, and gender, there is a clear causal relationship between vitamin D status and depression among the healthy general population and establishing that Vitamin D is crucial to mental health [15][16][17][18][19][20]. Regardless of this sufficient evidence, biological mechanisms coupling Vitamin D levels and mental health status are still not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Items on the PSS are rated on a 5-point scale ranging from “never” (0) to “almost always” (4). PSS-10 scores range from 0 to 40, and scores of 20 or greater are considered higher stress indicative of therapeutic help [ 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%